2020
DOI: 10.1016/j.semarthrit.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical course of COVID-19 in patients with rheumatologic diseases: A population-based study

Abstract: Objectives Patients with rheumatologic diseases might be more susceptible to COVID-19 and carry a poorer prognosis. The aim of this study is to examine the incidence and outcomes of all COVID-19 patients with rheumatologic conditions in Hong Kong. Methods This is a population-based retrospective study. All patients tested positive for SARS-CoV-2 by PCR with a previous diagnosis of rheumatologic diseases were reviewed. The incidence of COVID-19 in patients with rheumatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
1
26
1
1
Order By: Relevance
“…Although prevalence of certain chronic conditions such as diabetes in patients with COVID-19 infection has been studied [9], there was initial paucity of published incidence of COVID-19 infection in patients with rheumatology conditions. A recent study in Hong Kong showed incidence of COVID-19 in rheumatology patients similar to incidence seen in their general population (0.0126% in patients with rheumatologic diseases, compared to 0.0142% in the general population) [10]. Their estimated incidences were much lower than those we are reporting in this study, but differences in local testing protocols and reporting methodology may mean that these results are not directly comparable.…”
Section: Discussioncontrasting
confidence: 61%
“…Although prevalence of certain chronic conditions such as diabetes in patients with COVID-19 infection has been studied [9], there was initial paucity of published incidence of COVID-19 infection in patients with rheumatology conditions. A recent study in Hong Kong showed incidence of COVID-19 in rheumatology patients similar to incidence seen in their general population (0.0126% in patients with rheumatologic diseases, compared to 0.0142% in the general population) [10]. Their estimated incidences were much lower than those we are reporting in this study, but differences in local testing protocols and reporting methodology may mean that these results are not directly comparable.…”
Section: Discussioncontrasting
confidence: 61%
“…In a study from the USA, a higher incidence of COVID-19 infections in ARD patients of Latin origin (17.97%) was found with respect to those of non-Latin origin (4.69 to 5.89%); the non-ARD Latin patients also had a higher infection rate than the non-Latin ones (1.54 to 3.43%) patients [ 21 ]. By contrast, in a study from China, a higher incidence of COVID-19 in the general population as compared to ARD patients (0.0142 vs 0.0126%) [ 22 ] was found. Finally, a systematic review and meta-analysis of 26 observational studies showed that patients with ARD had an increased risk of developing COVID-19 compared with the general population [ 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…Meta-analysis of fourteen studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] showed that patients with RD had a significantly higher risk of developing COVID-19 than the general population (OR = 1.53, 95% CI 1.24-1.88, P = 0.000; I 2 = 62.4%, P = 0.001) ( Fig. 2).…”
Section: Risk Of Covid-19 Infection In Rheumatic Diseasesmentioning
confidence: 99%